Image Indexing: Challenges & Approaches - Javad Abbas Pour (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2007)
Some of the library & information science as well as computer specialists are considering image indexing as one of the best ways for the appropriate image storage and retrieval. Therefore each, of them has tried to use different approaches and methods for image indexing. Although their efforts have solved some Problems of image indexing. Because of the unique features of images that distinguish them from other documents, these efforts have not been highly successful. In this article it is tried to mention some of the difficulties that image indexers encounter. In addition, it is pointed to some of the methods used by both librarians and computer specialists, considering advantages and disadvantages of each method.